Interphase mechanical behavior of carbon fiber reinforced polymer exposed to cyclic loading. (20th October 2017) - Cole, Daniel P.; Henry, Todd C.; Gardea, Frank; Haynes, Robert A.
Abstract: A micro-/nano-scale technique is presented for characterizing early stage damage formation on un-sized individual carbon fibers as well as embedded carbon fibers exposed to cyclic loads. Nanoindentation and atomic force microscopy were used to study the local mechanical properties and morphology of composite constituents before and after cyclic loading. Samples were of the type: 1) un-sized individual carbon fiber and 2) carbon fibers embedded in an epoxy matrix. Contributions from the structural compliance were isolated from the indentations in order to track variations in interphase properties due to global fatigue. When tested in the radial direction, the fiber shell was found to be approximately 50% stiffer than the fiber core. Indentations on fibers within a composite cycled to 100% of fatigue life revealed a compliance effect of roughly 5 GPa with respect to fibers within a control composite. The experimental results are compared to a finite element analysis model in order to help understand the mechanical influence of the interphase in the presence of the elastically-mismatched fibers and matrix. The work is a first step toward understanding damage precursor formation in individual microfibers and composite interphase regions; the work is expected to enable multiscale composite modeling efforts as well as the development of future self-sensing materials.